Nusantara Optometrist Information Management System - Mohd Zabri, Nur Izzati Hadawiah; Hamzah, Dr Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2022)
Nusantara Optometrist Information Management System is a system that serves to manage customer information, products, and stocks with more systematic and efficient. The current habit of centering glasses still uses the manual method of storing information into files. Among the problems that exist in the existing system are customer data information and stock recorded manually, systematic stock management, overlap of data information and long time to complete tasks. Due to this problem, owners and managers find it difficult to decide what to plan ahead for. Therefore, the web-based information management system was developed to overcome the problem and help to produce useful reports. The prototype methodology has been selected for use in the development of this system as it corresponds to the medium size of the project. The system was developed using Visual Studio, Xampp, Window 10 operation and PHP programming language (Hypertext Preprocessor). This system is expected to store customer information at all Nusantara Optometrist branches as well as facilitate the task of staff to record bookings and payments made by customers. Therefore, this system will help Nusantara Optometrist improve information management and productivity.